Perceptions of sugar-sweetened beverages among adolescents in North Carolina - Haynes-Maslow, Lindsey; Ray, Sarah; Giombi, Kristen (Frontiers in Public Health, 2022)
Introduction: Sugar-sweetened beverage (SSB) consumption among adolescents contributes to diet-related chronic disease including obesity, type 2 diabetes, and poor oral health. Objective: To better understand adolescents’ perceptions, attitudes, and consumption behaviors around SSBs by conducting virtual workshop discussions with adolescents in NC. Materials & Methods: Adolescents ages 11-17 in communities with a high proportion of Supplemental Nutrition Assistance Program (SNAP) eligible households were selected to participate in a series of virtual group workshops during summer 2021. A semi-structured discussion guide was used by a workshop facilitator. Workshop discussions centered around general health perceptions, SSB perceptions, and consumption behaviors. A thematic analysis was used to summarize knowledge, beliefs, attitudes, and perceptions around SSBs. Results: Approximately 36 adolescents participated across four group workshops. Parents and caregivers influenced adolescents most when it came to making beverage choices. Positive SSB perceptions included liking the taste and the association with special times and social events. Negative opinions focused on associated health risks (diet-related chronic disease and poor oral health). Some adolescents acknowledged SSBs were not healthy but suggested they could be consumed occasionally. Very few participants mentioned any benefits from SSBs; those that mentioned benefits stated they provided energy, replaced electrolytes, and tasted good. Conclusion: Findings provide several key insights that can contribute to the development of messages aimed at curbing SSB consumption among adolescents. For example, messages that focus on catching adolescents’ attention and sharing short- and long-term health consequences of high SSB consumption resonated with adolescents, but because occasional SSB intake was not seen as consequential, messages that suggest abstinence from SSBs may not be helpful in reducing consumption.